Literature Review: Peran Guru dalam Membangun Generasi Berpikir Kritis-Strategi Pengembangan Keterampilan Abad 21 - Islawati, Islawati; Samsuddin, Yati Bt (Indo-MathEdu Intellectuals Journal, 2025)
The role of teachers in developing students' critical thinking skills has become increasingly crucial in 21st-century learning. This study aims to review various strategies employed by teachers to enhance critical thinking skills using a Systematic Literature Review (SLR) approach. Data were collected from 13 peer-reviewed international journals, selected based on their relevance to the topic, research methods, and impact on students' critical thinking skills. The data analysis technique used was thematic analysis, which allowed for identifying patterns and key findings from previous studies. The results indicate that Project-Based Learning (PBL), group discussions, and the integration of digital technologies such as Augmented Reality and Artificial Intelligence are effective strategies for fostering students' critical thinking. However, implementing these strategies faces challenges, including limited technological infrastructure, insufficient teacher training, and educational policies that do not fully support innovative learning methods. Therefore, strengthening teacher training, curriculum reform, and improving access to technology is essential to ensure these strategies can be effectively and sustainably implemented in the education system.